Long-Term Follow -Up After Radiofrequency Catheter Ablation of Fascicular Ventricular Tachycardia at National Institute of Cardiovascular Diseases - Ali, MA; Hossain, MM; Hashem, S; Jami, MA; Hossain, A; Foran, JP; Ahmed, R (Cardiovascular Journal, 2011)
Introduction: Verapamil-sensitive, idiopathic left ventricular tachycardia (ILVT) with right bundle branch block configuration and left-axis deviation is known to be due to re-entry mechanism but the exact nature of reentrant circuit in ILVT is not fully elucidated. In this study we evaluate the results of long-term clinical outcome in patients who underwent radiofrequency catheter ablation of idiopathic fascicular ventricular tachycardia in National Institute of Cardiovascular Diseases. Methods: Electrophysiological studies and radiofrequency ablation were performed in 46 consecutive patients (42 men,04 women), age ranging from 16 to 36 years (mean 20±5 years) with verapamilsensitive ILVT and structurally normal hearts. VT could be terminated by the intravenous administration of verapamil in all patients. Mapping was performed using a Bard electrophysiology system. The target site for ablation was the mid-septum of left ventricle where the earliest Purkinje potentials were recorded during VT. RF current was applied to the target site with or without late diastolic potential during VT in all patients to meet the ablation endpoints which were termination of the VT and non-inducibility of the tachycardia. Results: All 46 patients had successful ablation of the ILVT. During 3 years follow up 02 patients had recurrence. Conclusion: Idiopathic left ventricle tachycardia occurs most commonly in young population. Prompt recognition of this arrhythmia is important since radiofrequency ablation can cure this rhythm problem. This can be achieved in a country like Bangladesh where resources are limited. Key words: Radiofrequency Catheter ablation; Idiopathic left ventricle tachycardia. DOI: http://dx.doi.org/10.3329/cardio.v1i2.8239 Cardiovasc. j. 2009; 1(2): 201-206